How fares the "commanding heights" of the Swiss economy? Evidence from the Crux of Capitalism project - Magaly Abboud; Fabio Bernasconi; Sára Czégé; Camilla Erencin; Simon J. Evenett; Felix Reitz (Aussenwirtschaft, 2023)
The track record of Swiss publicly listed companies in creating economic value is assessed, along with their propensity to experience corporate distress. This assessment is conducted both in absolute terms and relative to foreign peers for the years 2005 to 2022. Established measures of corporate distress are augmented by a specially constructed economic profits measure assembled from quarterly financial reports. While on average Swiss firms perform better in economic profit terms than rivals from neighboring countries, there are doubts as to whether Swiss firms can generate higher levels of economic profit in the future, especially as the cost of capital is rising.
Keywords: G32; G33; E43; E44; E58; 330; economic profits; economic value creation; corporate distress; bankruptcy; Switzerland